Analisis Potensi Sumber Daya Air Daerah Aliran Sungai (DAS) untuk Kebutuhan Irigasi Padi dan Palawija di Kecamatan Pesisir Tengah Kabupaten Pesisir Barat - Kurniadi, Riko; Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi (abe.fp.unila.ac.id, 2024)
The purpose of this study was to determine the potential of water resources in the Way Ngison Kiri irrigation area which has an area of 44.47 ha of rice fields for irrigation water needs for rice and peanut crops so that the optimal planting area is obtained with the right cropping pattern and distribution of irrigation water. The data used in the analysis of water resource potential for watersheds (DAS) for irrigation water needs include irrigation water needs for rice and groundnut crops, mainstay discharge, crop water requirements or consumptive use, and land water balance from the results of the SWAT simulation (Soil and Water Assessment Tool). The use of ArcGIS SWAT analysis as a geographic information system that makes it easier to manage and perform data analysis. Based on the results of the analysis that the maximum value of irrigation water requirements in the first planting season (MT I) was 1.03 m3/s occurred on the last 15 days of January, in the second planting season (MT II) 1.1 m3/s occurred on 15 the last day of May, while the third planting period (MT III) was 1.08 m3/sec which occurred on the 15th day of early June. Overall, in the first to third planting season, the mainstay discharge value is fulfilled, because the mainstay discharge value is greater than the value of water demand. Based on the adequacy of irrigation water, the optimal planting area for rice and secondary crops is 11 ha and the recommended method of irrigation water distribution is by group method. Keywords: Irrigation water needs, Mainstay discharge, SWAT, Watershed